Membangun Kesadaran Mahasiswa Melalui Edukasi Dampak Perilaku Menyimpang Bagi Prestasi Akademik di Asrama GKI LIBORANG - Yuliana Patinama; Agustina Ivone Poli; Leny M. Manalip; Retno Angraeni S. (Jurnal SOLMA, 2026)
Background: This event was motivated by concerns about the increase in deviant behavior among students, such as misuse of time, alcohol consumption, promiscuity, and lack of study discipline. These behaviors often disrupt concentration, reduce learning motivation, and ultimately impact low student academic achievement. This activity aims to increase dormitory students' understanding of various forms of deviant behavior that often appear in everyday life, as well as their negative impact on academic achievement. Method: This activity used interactive lectures, group discussions, and case studies. This activity was also complemented by reflection sessions and the preparation of individual action plans to encourage positive behavioral changes. Results: The results showed increased participant awareness of the importance of maintaining behavior in accordance with academic and spiritual values. Participants began to demonstrate a commitment to building a conducive learning environment that supports achievement. Through this community service counseling activity, students can benefit: a) increased knowledge of the importance of education and maintaining positive cultural values ​​to prevent deviant behavior. b) increased awareness of students as a generation of development to avoid or prevent deviant behavior because it can affect academic achievement. Conclusion: This activity is expected to serve as an initial step toward fostering a healthier, more disciplined, and achievement-oriented dormitory culture. Collaboration among various parties is essential to create a dormitory environment that is conducive to and supportive of academic achievement.